Problems of local budgets’ organization in Ukraine in the context of financial decentralization (World of finance, 2019)
Introduction. Fiscal decentralization as the main vector of development of Ukraine in general and local government in particular has set scientific and expert community task of defining feasibility and effectiveness of the reforms and their compliance with requirements and needs of society.Purpose. Analysis of the tool of organization of local budgets in Ukraine due to decentralization process to define the main results of these innovations and make recommendations for improving the system.Results. Specific features of organization of local budgets in Ukraine in terms of local government reform are observed. It is made comparative analysis of formation and execution of local budgets before and after the reform. Peculiarities of formation of the revenue of local governments are examined. Tax revenue is defined as the main source of local budgets. It is analyzed the main characteristics of collection of major budget-taxes. The features of expenditure policies at the local level are investigated. The main problems of this process are defined. It is investigated the place and role of intergovernmental transfers as a part of local budgets. The features of forming of intergovernmental transfers and horizontal fiscal equalization of local budgets in consequence of financial decentralization are determined. General conclusions resulting from the study are made.Conclusion. Reform of the system of local budgets requires a comprehensive update of local government and simultaneous implementation of sectoral reforms. In the system of local budget revenues development and selection of algorithm of formation of a well-defined orientation to ensure financial autonomy and financial viability and its implementation on an ongoing basis is a priority. The task of reforming expenditure part of local budgets is orientation of financial resources to secure capital expenditures and implementing their own powers of local government.